The Emerald guide to Ann Oakley - Crow, Graham (Emerald Publishing Limited, 2024)
The Emerald Guide to Ann Oakley offers a comprehensive guide to reading and understanding the development of Oakley's sociological ideas, placing them in the context of her life and her ground-breaking research into domestic and gender sociology. Ann Oakley delved into researching gender disparities, challenging prevailing ideas by distinguishing between sex and gender. Influenced by personal experiences, she questioned societal norms around marriage, motherhood, and gender roles. This volume takes a chronological and biographical approach in illustrating the development of Oakley's ideas and interests over the course of her career and personal experience exploring the challenges of societal gender dynamics. Essential reading for students and those new to Oakley's work, The Emerald Guide to Ann Oakley is a readable, clear, and comprehensive overview of her work, conveying her deep influence on contemporary social thought.
Keywords: Oakley, Ann -- Criticism and interpretation.; Sex -- Research -- Sociological aspects.; Sex role -- Research.; Social Science -- Gender Studies.; Gender studies, gender groups.; elektronické knihy; electronic books